BIRDS AT SEBYAR RIVER, ARANDAY, BINTUNI, WEST PAPUA - Freddy Pattiselanno; Agustina Yohanna Setyarini Arobaya; Alfredo Ottow Wanma (Scripta Biologica, 2018)
The River Sebyar is known as the home for particular aquatic birds and the wintering ground for migrant birds. The mass transportation along the river most likely impacted by the presence of wildlife species including birds. The research investigated the presence of water birds along the river. The study was done at six villages along the River Sebyar at the Aranday District of Bintuni Bay Regency of West Papua. The methods involved direct observation to the study sites by canoe-transect line along the river length with the assistance of binoculars, taxonomic description guide, and daily diary updated. Twenty-three birds were observed during the survey. Ten out of 23 bird species recorded in this survey have been observed that consisted of five species of Ardeidae, four of Anatidae, and one of Laridae. The escalation of human activities along the riverside especially during sago harvesting and a busy boat traffics within the Bintuni Bay tended to decrease spaces for particular bird species that usually occupied the areas for roosting and foraging assemblages.